The Impact of Fuel Oil Price Fluctuations on Indonesia's Macro Economic Condition - Akhmad, Akhmad; Romadhoni, Buyung; Karim, Kasnaeny; Tajibu, Muhammad Jibril; Syukur, Muhammad (International Journal of Energy Economics and Policy, 2019)
Since the beginning of the new order government up to now, Indonesia's economic development constantly influences by fluctuation in fuel oil price. This paper aims to know the impact of fuel oil price change on economic growth, inflation, and poverty in Indonesia using Vector Auto Regression (VAR) method. Data used in the research are quarterly time series data for 1980-2017 period. The research result indicates that an increase in fuel oil price gives negative impact on Indonesia's economy. Therefore, the government as well as all stakeholders needs to cooperate to reduce the negative impact of fuel oil price on economy. Keywords: Fuel Oil price, Economic Growth, Inflation, Poverty JEL Classifications: C32, Q43, Q48 DOI: https://doi.org/10.32479/ijeep.7470